2007
DOI: 10.1002/hep.21712
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic hepatitis C virus genotype 1 with peginterferon, ribavirin, and epoetin alpha

Abstract: Successful treatment of chronic HCV with peginterferon (PEGIFN) and ribavirin (RVN) is often limited by anemia. We performed the present study to determine if utilizing epoetin alpha (EPO) with or without a higher dose of RVN could enhance sustained virologic response (SVR). We randomized 150 treatment-naive patients with chronic HCV genotype 1 into 3 treatment groups: (1) PEGIFN alpha-2b (1.5 g/kg/week) ؉ weight-based RVN (WBR) 13.3 mg/kg/day (800 to 1400 mg/day); (2) PEGIFN alpha-2b ؉ WBRVN ؉ EPO (40,000 U/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
139
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 31 publications
(49 reference statements)
10
139
3
3
Order By: Relevance
“…The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Discussionsupporting
confidence: 62%
“…However, some studies have used decision analysis to estimate the cost-effectiveness of adjunctive therapy with erythropoietic growth factor (EGF) compared with that of standard care in the treatment of hepatitis C. The use of EGFs appears to be costeffective in patients with anaemia who are receiving combination therapy for HCV genotype 1, 2 or 3. Compared with The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Resultssupporting
confidence: 41%
See 1 more Smart Citation
“…6,7 The most recent trial did not find that the use of growth factors improved sustained virologic response (SVR) with standard doses of peginterferon-␣ and ribavirin. 8 Only when growth factors were combined with higher ribavirin doses was an improvement in response rate observed.…”
mentioning
confidence: 99%
“…Lower response rates are often observed when clinical trial data is translated into clinical practice, but these results ultimately mean that the Shiffman study may not support the use of growth factors given the SVR threshold of 50% declared by Del Rio. 8 In addition to concerns about the efficacy, these limited data sets have hindered the ability to establish safety in the HCV population. Red cell aplasia has been reported during erythropoietin therapy in at least one hepatitis C patient, and rapid rises in hemoglobin or targeting higher hemoglobin levels have been associated with an increased tendency to thrombotic episodes, a concern that is reflected in the package labeling for these agents.…”
mentioning
confidence: 99%